The Study of musculoskeletal health problem among bankers in Kathmandu valley - Adhikari, Luna Kiran; Chaudhary, Pramodh; Sangroula, Raj Kumar; Thapaliya, Roja; Thapa, Janak Kumar (International Journal Of Community Medicine And Public Health, 2023)
Background: Musculoskeletal disorders affect all persons regardless of age and sex and are prevalent across a wide range of industries and jobs. In Asian populations, a high annual prevalence of Work-related Musculoskeletal Disorder in at least one body region is varied from 40% to 95%. The aim of this study was to assess the prevalence and identify the factors contributing to Musculoskeletal disorders. Methods: Analytical cross-sectional and quantitative method was used. Random sampling was used to select the banks and convenience sampling was used to select the branches of those selected banks and finally, the census technique was used to collect the data from respondents. A structured questionnaire was designed and administered to study participants. Data collected from respondents were entered into Epidata 3.1 and were analysed and expressed using SPSS 26. Results: The study showed the annual prevalence of Musculoskeletal disorder was 82.5% with the highest single MSDS prevalence of neck pain and the previous one-week prevalence rate was 37.6%. Gender (OR=2.543, 95% CI=1.082-5.974), age group 30-39 (OR=2.430, 95% CI=1.060-5.572, Physical activity (OR=7.379, 95% CI=3.004-18.12), Experience (OR=5.27, 95% CI=2.490-11.185), Repetitive task (OR=22.208, 95% CI= 9.744-50.617), Posture (OR=3.834, 95% CI=1949-7.543), Working hours (OR=2.06, 95% CI=1.070-3.966) were found to be significantly associated with MSDs. Conclusions: Occupational Health and safety was one of the neglected areas in Banking industry. The concept of occupational safety and health is still new in Nepal.